How cultural strategic management supports the sustainability of Selasar Sunaryo Art Space in the Indonesian artistic field - Yohanes Rian Yustianto; Agung Hujatnika (Journal Albion : Journal of English Literature, Language, and Culture, 2025)
This research explores the role of long-term strategic management planning in sustaining the Selasar Sunaryo Art Space in the Indonesian artistic field. It looks at how an arts institution stays afloat for 25+ years despite ongoing funding struggles. Using the approach of qualitative research, the study relies on deep interviews with several key actors, participatory observation, and a literature study. It is based on Henry Mintzberg’s concepts of emergent and deliberate strategies concerning planned action and adaptability to change. It also involves Pierre Bourdieu’s artistic field theory, understood through the lenses of Michael Grenfell and Hans van Maneen, examining the conflict between autonomous and heteronomous forces of the artistic world. The report’s most notable conclusion is the need to create institutional structures with flexibility and resilience. The study concludes that long-term sustainability in the artistic field depends on a strategy that is both structured and flexible, balancing artistic ideals with real-world challenges.